Methodological path to the genesis of a digital translation - Fan, Lingjuan (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2016)
Because online digital writing has become an important means of text production, this paper argues that the core concept of genetic criticism, ‘avant-texte’, should be kept up-to-date with the new medium and environment. It will show how online comments in interactive and collaborative textual production should be recognized within the translation’s genesis. The online comments on a widely read news translation in China’s largest virtual translation community is used to showcase how these digital comments can be identified and examined to facilitate our understanding of the microhistory or genesis of news translation. Situated at the juncture of genetic criticism and translation studies, this paper concludes by addressing theoretical and methodological implications for conducting a genetic analysis based on the proposed analytical model.